Efficacious and safe orotracheal intubation for laboratory mice using slim torqueable guidewire-based technique: comparisons between a modified and a conventional method. Issue 1 (December 2015) - Su, Chieh-Shou; Lai, Hui-Chin; Wang, Chih-Yen; Lee, Wen-Lieng; Wang, Kuo-Yang; Yang, Ya-Ling; Wang, Li-Chun; Liu, Chia-Ning; Liu, Tsun-Jui
Abstract Background Tracheal intubation of laboratory mice remains essential yet challenging for most researchers. The aim of this study was to investigate whether this procedure can be more efficiently and safely accomplished by a novel method using slim and torqueable guidewires to guide access to the trachea. Methods This study was carried out in an animal laboratory affiliated to a tertiary medical center. Mice weighing 22 to 28 g were subjected to various open-chest experiments after being anesthetized with intraperitoneal ketamine (100 mg/kg) and lidocaine hydrochloride (10 mg/kg). The oropharyngeal cavity was opened with angled tissue forceps, and the trachea was transilluminated using an external light. The vocal cords were then crossed using either the Conventional method with a 38-mm-long, end-blunted stiff needle as a guide for insertion of a 22-gauge, 25-mm-long intravenous catheter into the trachea, or the Modified method utilizing using a 0.014-inch-thin torqueable wire as the guide to introduce an identical tube over it into the trachea. The epithelial integrity of the trachea was later examined histologically when the animals were sacrificed either immediately after the surgery or at 28 days post-surgery, depending on the corresponding research protocols. Results Orotracheal intubation was successfully completed in all mice using either the Conventional (N = 42) or the Modified method (N = 50). With the Modified method, intubation took less time (1.73 vs. 2.17 min, Modified vs. Conventional, p < 0.001) and fewer attempts (1.0 vs. 1.33, p < 0.001), and there were fewer procedural difficulties (0 % vs. 16.7 %, p = 0.009) and complications (0 % vs. 11.9 %, p = 0.041) compared with the Conventional method. Histological analysis revealed a significantly lower incidence of immediate (0 % vs. 39 %, p < 0.001) and late (0 % vs. 58 %, p < 0.001) injuries to the tracheal epithelial lining with the Modified method compared to the Conventional method. Conclusions Tracheal intubation for laboratory mice can be completed efficiently, safely and atraumatically using the proposed Modified method employing readily available inexpensive instruments.